The MEL program for the atomistic modeling of functional layers in solar cells - Grigoriev, F.V.; Romanov, A.N.; Sulimov, V.B.; Sulimov, A.V.; Oferkin, I.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2012)
A new method for the atomistic modeling of periodic structures formed by organic and hybrid molecules is proposed. These structures are used to manufacture the organic and hybrids solar cells. In the framework of this method, the energy of interatomic interaction is calculated using the classical force field. The search of the most stable periodic configurations is performed using a genetic algorithm for the global optimization. A software implementation of the method is described. The efficiency of the proposed parallel version is analyzed. The test calculations of the periodic structure based on the fullerene molecule are discussed.